Removal of pyrene in simulated wetland by joint application of Kyllinga brevifolia Rottb. and immobilized microbes. (October 2016) - Wang, Chuanhua; Gu, Lingfeng; Liu, Xiaoyan; Ge, Shimei; Chen, Tingru; Hu, Xiaoxin
Abstract: The objectives of this study were to evaluate the effects of plant and immobilized microbes on pyrene removal and soil microbial functional diversity of co-contaminated soil. The results indicated that the dissipation ratios of pyrene in the soil with plant (P), soil with immobilized microbes (IM) and soil with both of them(PIM) were 51.5 ± 0.69%, 55.2 ± 3.8%, 63.2 ± 1.29% respectively, and were higher than CK (31.2 ± 1.5%) with neither of them. Soil microbial functional diversity was assessed by the community-level physiological profiles (CLPP) using Biolog Eco-plates. The Biolog results revealed that the metabolic intensity in the rhizospheric soil marked P-R and PIM-R was significantly higher than that of non-rhizospheric soil and the CK during the incubation period. A similar variation in the diversity indexes (Shannon, Simpson and McIntosh) was observed. Principal component analysis (PCA) of the distribution of carbon substrate utilization for all treatments suggests that the microbial community catabolic diversity is different. Among the carbon utilization profile, carbohydrates were the main carbon source of the sample soil and IM increased the potential utilization of two substrate groups (phenols and carbohydrates) more strongly than that of the other groups. Graphical abstract: Though bioremediation of co-contaminated soils has been studied widely, rare literatures have expounded using immobilized microbe and no literature about Kyllinga brevifolia Rottb. Pyrene removal, pyrene accumulation in K . brevifolia Rottb., microbial functional diversity and microbial community structure in the rhizosphere of different treatments (plant with and without IM) were explored in this paper through a pot experiment. Compared with non-rhizospheric soil and CK, the rhizosphere of joint application of K. brevifolia Rottb. and IM has better effect than single of them for pyrene removal and improving microbial functional diversity. Highlights: Embedding microbes combined with Kyllinga brevifolia Rottb. enhanced pyrene removal. Microbial functional diversities were enriched in rhizosphere with embedded microbes. The highest utilization of carbon sources occurred for soils from P-R and PIM-R.